Synthesis and Evaluation of Novel 3‐Allylseleno‐6‐Alkylsulfonylpyridazine Derivatives with Potential Anticancer Properties - Kim, Chaewon; Park, Myung‐Sook (Bulletin of the Korean Chemical Society, 2017)
A new series of 3‐allylseleno‐6‐alkylsulfonylpyridazines and 3‐allylseleno‐6‐alkylsulfinylpyridazines were synthesized from 3,6‐dichloropyridazine for anticancer agent development. The inhibitory effects of 3‐allylseleno‐6‐alkylsulfonylpyridazines on human cancer cell lines were investigated. The synthesis involved thiolation, oxidation, selenylation, and Se‐allylation of alkylthiols. That is, sodium methanethiolate, ethanethiol, propanethiol, butanethiol, pentanethiol, and hexanethiol were inserted into the 6‐position of the pyridazine nucleus. These new synthetic compounds exhibited antiproliferative activity against human breast cancer (MCF‐7), hepatocarcinoma (Hep3B), and human colon carcinoma (RKO) cells in CCK‐8 assays, and are potential candidates for cancer chemotherapy.